Tandem mass tag‐based proteomic analysis of endoplasmic reticulum proteins in mulberry leaves under ultraviolet‐B and dark stress. Issue 2 (24th March 2022) - Liu, Shengzhi; Ou, Yuting; Li, Yaohan; Sulaiman, Kaisa; Tao, Minglei; Shawky, Eman; Tian, Jingkui; Zhu, Wei
Abstract: Mulberry leaves have been used in traditional Chinese medicine due to their antioxidant, antidiabetic, and antihyperlipidemic properties. A previous study showed that ultraviolet‐B radiation followed by dark incubation could improve the contents of active ingredients in mulberry leaves, such as moracin N and chalcomoracin. The endoplasmic reticulum (ER) serves as a protein quality control center and the location for protein synthesis, which is involved in the response to the environmental stress in plants. To investigate the mechanisms in response to ultraviolet‐B radiation followed by dark incubation (UV + D), ER proteomics was performed on mulberry leaves. The ER protein markers, glucose‐regulated protein (GRP78), and calnexin (CNX), were significantly higher in the ER fraction than in the total protein fraction, indicating that the ER was purified. Compared to the control, the abundance of protein disulfide isomerase, UDP‐glucose glycoprotein glucosyltransferase, CNX, and calreticulin proteins decreased, while of the abundance of heat shock‐related proteins increased under stress. P450 enzyme system‐related proteins and ribosomal proteins showed significant increases. These results suggest that under UV + D stress, mulberry leaves activated the cell redox and ER quality control systems, enhancing protein synthesis and weakening N ‐glycan biosynthesis in the ER to resist the damage.